Participatory Rural Planning Empirical Study on the Role of Villagers in Planning Rural Development - Mehrān Alalhesābi (مسکن و محیط روستا, 2011)
5 Participation of villagers in preparing and implementing development plans is an issue taken into consideration by many researchers working in the field of rural studies as well as the responsible people engaged in rural implementation affairs. In this regard, along with a variety of methods and experiences of rural planning, the issue of people's participation in preparation and implementation of these plans is assumed to be inevitable and necessary for many years, and its observation is recommended. But the fact is that either the planning and implementation process in rural areas generally exclude the role of villagers completely or the villagers’ participation does not occur in its true meaning and is pretty superficial or in the most optimistic mode, their participation is quite a symbolic device used by officials to, give legitimacy to the project. Despite all the concerns and unsuccessful experiences of those types of rural planning, in which the collaboration and participation of villagers had been considered, ultimately the open and unanswered question is that whether the villager’s participation in planning their own settlements is really achievable today with regard to all social, economic, cultural and executive restrictions or not. And how is people's participation in preparation of rural development plans possible? How, and with what programming procedures and in what fields, is the participation of villagers really feasible? What tools could be effective to extend the rate and range of participation? Starting with raising the above questions and planning to find their answer, and considering the importance of local public participation in rural development plans, the present paper tries to present all the features of the rural planning implemented with villagers’ participation and introduce the participatory planning as something uncomplicated and possible. In this regard, describing the experience of fabric planning of some parts of Bandar-e Loft in Qeshm Island, the paper explains that people should determine the objectives and policies of the plan and help planners and designers achieve these goals through consultation. In addition, if experts do their task properly, they can also give consultation to rural villagers regarding their development plans. Villagers may have not entered higher levels of participation like spontaneity and self-determination however, the task of planners, designers, managers, policy makers and officials is to provide the ground to facilitate this spontaneity, and helping villagers to have an active participation.